Prevalence and risk factors associated with stroke in hypertensive patients: a hierarchical analysis. - Saraiva da Silva, Erisonval; Pereira Borges, José Wicto; Magalhães Moreira, Thereza Maria; Pacheco Rodrigues, Malvina Thais; Caetano de Souza, Ana Célia (Revista de Enfermagem Referência, 2020)
Background: Stroke causes permanent sequelae and is the second leading cause of death worldwide. Poor blood pressure control corresponds to 80% of cases. Objective: To analyze the prevalence and identify the risk factors for stroke in hypertensive patients using a hierarchical analysis. Methodology: Cross-sectional study involving 378 hypertensive patients living in a municipality of Southern Piauí, Brazil, in 2018. Sociodemographic variables, health conditions, and lifestyles were analyzed using hierarchical multiple regression organized at distal, intermediate, and proximal levels, respectively. Results: Stroke prevalence was 11.6%. Associated factors were: gender (AOR = 0.47; 95% CI: 0.23- 0.95) and age (AOR = 1.03; 95% CI: 1.01-1.06) at the distal level; having a relative who has had a stroke (AOR = 2.01; 95% CI: 1.00-4.04) and going to the emergency room with altered blood pressure (OR = 2.01; 95% CI: 1.00-4.05) at the intermediate level; intake of high-fat foods (OR = 2.33; 95% CI: 1.15-4.72), intake of sweets (OR = 2.37; 95% CI: 1.15-4.90), and time as a smoker (OR = 1.02; 95% CI: 1.00-1.04) at the proximal level. Conclusion: Prevalence was explained by a hierarchy of risk factors, thereby evidencing those classi- fied as modifiable proximally.